Pekerjaan dan Dukungan Sosial Terhadap Breastfeeding Self Efficacy Ibu Post Partum - Risma Aliviani Putri; Moneca Diah Listiyaningsih; Fiktina Vifri Ismiryan (Universitas Ngudi waluyo, 2022)
The exclusive breastfeeding program continues to be intensified as one of the efforts to reduce stunting in Indonesia. Data on exclusive breastfeeding in babies 0-6 months in Indonesia in 2019 amounted to 66.69% and decreased to 66.1% in 2020. Many factors affect exclusionary breastfeeding including work and social support to breastfeeding mothers. The purpose of this study is to determine the relationship between work and social support to the self-efficacy of post partum mothers.The research design uses descriptive studies with a cross-sectional approach. The sampling technique uses Purposive Sampling based on inclusion and exclusion criteria. The study population was all postpartum mothers treated at PMB Ignasia Tripuji Astuti, S.ST. Keb. The sample in this study was a puerperal mother who gave birth at PMB Ignasia Tripuji Astuti, S.ST. Keb. The results of this study showed that working mothers mostly had low Breastfeeding Self Efficacy, a total of 11 people (61.1%). While mothers with good social support mostly have high Breastfeeding Self Efficacy, a total of 14 people (82.4%). It is hoped that postpartum mothers and breastfeeding mothers can increase their self-efficacy as a result of the success of exclusive breastfeeding.Abstrak Program pemberian ASI eksklusif terus digencarkan sebagai salah satu upaya menurunkan stunting di Indonesia. Data pemberian ASI eksklusif pada bayi 0-6 bulan di Indonesia tahun 2019 sebesar 66,69% dan terjadi penurunan menjadi 66,1% pada tahun 2020. Banyak faktor yang mempengaruhi pemberian ASI eksklusif diantaranya pekerjaan dan dukungan sosial kepada ibu menyusui. Tujuan penelitian ini mengetahui hubungan pekerjaan dan dukungan sosial terhadap self efficacy ibu post partum. Desain penelitian menggunakan studi deskriptif dengan pendekatan cross sectional. Teknik pengambilan sampel menggunakan Purposive Sampling yang berdasarkan kriteria inklusi dan eksklusi. Populasi penelitian yaitu seluruh ibu postpartum yang dirawat di PMB Ignasia Tripuji Astuti, S.ST.Keb sejumlah 33. Sampel dalam penelitian ini adalah 30 ibu post partum yang melahirkan di PMB Ignasia Tripuji Astuti, S.ST.Keb. Hasil penelitian ini menunjukkan bahwa ibu yang bekerja sebagian besar memiliki Breastfeeding Self Efficacy yang rendah, sejumlah 11 orang (61,1%). Sedangkan ibu dengan dukungan sosial baik sebagian besar memiliki Breastfeeding Self Efficacy tinggi, sejumlah 14 orang (82,4%). Diharapkan ibu nifas dan ibu menyusui dapat meningkatkan self efficacynya sebagai upanya keberhasilan pemberian ASI Ekslusif